Regional techno‐economic and life‐cycle analysis of the pyrolysis‐bioenergy‐biochar platform for carbon‐negative energy. (30th August 2019) - Li, Wenqin; Dumortier, Jerome; Dokoohaki, Hamze; Miguez, Fernando E.; Brown, Robert C.; Laird, David; Wright, Mark M.
Abstract: This study investigates the sensitivity of greenhouse gas (GHG) emissions and the minimum fuel selling price for a 2000 metric ton day −1 integrated pyrolysis‐bioenergy‐biochar platform with respect to the biorefinery location and biomass types. The regional techno‐economic and life‐cycle analysis is evaluated in three US counties using representative crops: rice in Glenn County (California), corn in Hamilton County (Iowa), and peanuts in Jackson County (Florida). We evaluate the biochar selling price considering crop yield increases of 0.6%, 2.9%, and 10% after biochar application over 20 years in Glenn County, Hamilton County, and Jackson County, respectively. The biochar prices are calculated under low and high commodity prices to determine upper and lower bounds. Jackson County has the most economically beneficial scenario with an average minimum fuel selling price (MFSP) of 1.55 gal −1 of biofuel produced whereas Hamilton County has the highest average MFSP of 3.82 gal −1 . The life‐cycle analysis shows that woody biomass has a strong potential to produce carbon‐negative energy compared to grass and straw. Of the 304 cases scenarios considered for this platform, 64% could produce biofuel with negative GHG emissions, which would meet the Renewable Fuel Standard (RFS) target for cellulosic biofuels. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd